Dexamethasone for preventing postoperative nausea and vomiting after mastectomy. Issue 30 (24th July 2020) - Xu, LeiLai; Xie, XiaoHong; Gu, XiDong
Abstract: Background: Postoperative nausea and vomiting (PONV) is a common complication after mastectomy. Although many researches have been studied the prophylactic effect of antiemetics, none of the results are effective. To overcome this problem, dexamethasone was used to relieve the occurrence of PONV. Since concerns about steroid-related morbidity still remain, We carried out a meta-analysis to evaluate the impact of prophylactic dexamethasone on PONV, post-operative pain undergoing mastectomy. Methods: Literature search was conducted through PubMed, Web of Science, EMBASE, MEDLINE, and Cochrane library database till June 2019 to identify eligible studies. Meanwhile, we also consulted some Chinese periodicals, such as China Academic Journals, Wanfang and Weipu. The research was reported according to the preferred reporting items for systematic reviews and meta-analysis guidelines. Randomized controlled trials were included in our meta-analysis. Meanwhile, the assessment of the risk of bias was conducted according to the Cochrane Handbook for Systematic Reviews of Interventions version. The pooled data are processed by software RevMan 5.3. Results: Four studies with 490 patients were enrolled to this meta-analysis. Our study demonstrated that the dexamethasone group was significantly more effective than the placebo group in term of PONV (risk ratio [RR] = 0.46, 95% confidence intervals [CI]: 0.30–0.70, P  = .0003), nausea (RR = 0.26, 95% CI: 0.10–0.68, P  = .006) and vomiting (RR = 0.15, 95% CI: 0.04∼0.55, P  = .004). The visual analog scale score was significantly diminished at 1 hour (weighted mean difference = -1.40, 95% CI: -1.53 to -1.26, P  < .00001) in the dexamethasone group, while, no statistically significant difference was observed between the two groups in terms of visual analog scale at 24 hours (weighted mean difference = -0.56, 95% CI: -1.24 to 0.13, P  = 0.11). Conclusion: Not only does Dexamethasone reduce the incidence of PONV but also decreases postoperative pain. However, we still need larger samples and higher quality studies to determine the relationship between symptoms and administration time to reach the conclusion. Trial registration number: PROSPERO CRD 42018118575